(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
While starting a business alone (solopreneurship) presents numerous managerial advantages, it also comes along with multitudinous bottlenecks that have been reported to significantly reduce the chances of such businesses to thrive. An executive survey conducted in the Q4 of 2021 in Cameroon revealed that 73% of all SMEs in Cameroon are started by solopreneurs. While a similar rate of solopreneurship has been advanced by some authors for the United States of America, one of the leading economies globally, the reasons why entrepreneurs start alone in advanced economies, the ease of getting bank loans, as well as the general business environment in which such entrepreneurs evolve are quite different from those in francophone Central Africa, where entrepreneurs are much more often motivated by earning a living, are poorly skilled in terms of managerial skills, and struggle to find fundings. This paper sought to explicate the relationship between high rate of solopreneurship and high rate of business failure in francophone Central Africa. It states the hypothesis that the high rate of business dismals observed in this sub-region is linked to the high rate of solopreneurship also observed there. This paper’s objective is herewith to coax entrepreneurs of the Central African sub-region to leverage the strategical and financial preeminence of starting SMEs in joint ventures rather than alone.